Changes in PM2.5 sensitivity to NOx and NH3 emissions due to a large decrease in SO2 emissions from 2013 to 2018. Issue 3 (3rd May 2020) - XU, Guangyi; ZHANG, Qianqian; YAO, Yu; ZHANG, Xingying
ABSTRACT: The authors evaluated and compared the behavior of PM2.5 with respect to NO x and NH3 emission changes in high (the year 2013) and low (the year 2018) SO2 emission cases. Two groups of simulations were conducted based on anthropogenic emissions from China in 2013 and 2018, respectively. In each group of simulations, a respective 25% reduction in NO x and NH3 emissions were assumed. A sensitivity factor ( β ) was defined as the relative change in PM2.5 concentration due to 1% change in NO x or NH3 emissions. In the high SO2 emissions case, PM2.5 was more sensitive to NH3 (0.31) emissions change than NO x (0.21). Due to the significant decrease in SO2 emissions from the high to low SO2 emissions case, the sensitivity of PM2.5 to NO x increased to 0.33, while its sensitivity to NH3 decreased to 0.22. The result implies that now and in the future, PM2.5 is/will be less sensitive to NH3 emissions change, while NO x emissions control is more effective in reducing the surface PM2.5 concentration. Seasonally, in the low SO2 emissions case, the sensitivities of PM2.5 to NO x and NH3 in winter were higher than those in summer, indicating that to deal with severe winter haze more attention should be paid to the emissions control of inorganic PM2.5 precursors, especially NO x . Graphical abstract: